Electrophysiological evidence for functionally distinct neuronal populations in the human substantia nigra - Ramayya, Ashwin G.; Zaghloul, Kareem A.; Weidemann, Christoph T.; Baltuch, Gordon H.; Kahana, Michael J. (Frontiers in Human Neuroscience, 2014)
The human substantia nigra (SN) is thought to consist of two functionally distinct neuronal populations--dopaminergic (DA) neurons in the pars compacta subregion and GABA-ergic neurons in the pars reticulata subregion. However, a functional dissociation between these neuronal populations has not previously been demonstrated in the awake human. Here we obtained microelectrode recordings from the SN of patients undergoing deep brain stimulation (DBS) surgery for Parkinson's disease as they performed a two-alternative reinforcement learning task. Following positive feedback presentation, we found that putative DA and GABA neurons demonstrated distinct temporal dynamics. DA neurons demonstrated phasic increases in activity (250-500 ms post-feedback) whereas putative GABA neurons demonstrated more delayed and sustained increases in activity (500-1000 ms post-feedback). These results provide the first electrophysiological evidence for a functional dissociation between DA and GABA neurons in the human SN. We discuss possible functions for these neuronal responses based on previous findings in human and animal studies.